СРПСКО ПОДАНСТВО ЈОВАНА ДУЧИЋА (Prilozi za književnost, jezik, istoriju i folklor, 2023)
This paper is based on data from the archives of the official institutions of the Kingdom of Serbia, namely the Serbian Ministry of Interior’s Registry for the years 1907 and 1908 and the Belgrade City Administration’s Registry of Persons Granted the Serbian Citizenship. Due to a lack of documents and archival material destroyed in World War I, these formal registries were used as proof of completed administrative procedure for granting the citizenship of the Kingdom of Serbia to Jovan Dučić at his request. The paper also presents a facsimile of the Terazije Square hotels guest list on 3rd January 1907, featuring the name of Jovan Dučić, who had only just arrived in Serbia. In addition, the paper features a drawing of the Serbian Ministry of Interior building, torn down just before World War I, in which Dučić started his diplomatic career.